Acute kidney injury is associated with liver-related outcomes in patients with hepatitis B virus infection: a retrospective cohort study - Jiao Liu; Ruixuan Chen; Shiyu Zhou; Zhixin Guo; Licong Su; Lisha Cao; Yanqin Li; Xiaodong Zhang; Fan Luo; Ruqi Xu; Qi Gao; Yuxin Lin; et al. (BMC Nephrology)
Abstract Background The effects of acute kidney injury (AKI) on liver-related outcomes in patients with hepatitis B virus (HBV) infection remain unclear. The study aimed to evaluate the association between AKI with liver-related mortality and complications in patients with HBV infection. Methods The multicenter, retrospective cohort study included Chinese adults with HBV infection from 24 regional central hospitals between January 2000 and December 2022. AKI was defined as a ≥ 26.5 μmol/l increase in serum creatinine concentration within 48 h, or a ≥ 50% increase over the baseline within 7 days. The primary outcome was post-discharge liver-related mortality, while the secondary outcome was a composite of new-onset liver cirrhosis and hepatocellular carcinoma. Cox proportional hazard model was employed for analyses. Results Of the 86,204 inpatients with HBV infection and without liver cancer or cirrhosis at baseline, 4407(5.1%) patients experienced AKI. During a mean follow-up of 4.6 ± 2.4 years, 334 (0.4%) patients died of liver-related events. After adjustment, AKI during hospitalization was significantly associated with a higher risk of liver-related mortality after discharge (adjusted hazard ratio (HR), 1.78; 95% confidence intervals (CI), 1.26–2.51, P = 0.001), especially in those with severe AKI. Similarly, AKI was associated with a higher risk of cirrhosis or new-onset hepatocellular carcinoma (adjusted HR, 1.33; 95%CI, 1.10–1.60, P = 0.004). The association between AKI and liver-related outcomes remained consistent across different subgroups. Conclusions AKI during hospitalization was associated with substantial increased risk of liver-related mortality and incident liver-related complication. Our findings highlight the importance of monitoring AKI in patients with HBV infection for tailoring personalized treatments.